Tax reforms in EU Member States 2015. Tax policy challenges for economic growth and fiscal sustainability (Luxembourg, 2015)
"This annual report, prepared by the European Commission’s Directorate General for Economic and Financial Affairs and the Directorate General for Taxation and Customs Union, aims to make a contribution to discussions on tax policy in the EU through an analysis of tax policy challenges and recent reforms in the EU Member States."